Low Dose Hyperbaric Bupivacaine with Fentanyl in Spinal Anesthesia in Elective Cesarean Section - Regmi, Bharati Devi Sharma; Deo, Gopendra Prasad; Shrestha, Subin; Shrestha, Sabita; Mishra, Renuka Tamrakar (Journal of Chitwan Medical College, 2019)
Background: Spinal anesthesia with hyperbaric bupivacaine provides a dense neural block in cesarean delivery but associated with side effects like hypotension, bradycardia nausea and vomiting. Addition of low dose fentanyl with low dose of hyperbaric bupivacaine may decrease the incidence of these complications. The aims of study was to compare the hemodynamic parameters (blood pressure and heart rate), nausea and vomiting with low dose intrathecal hyperbaric bupivacaine with fentanyl vs a conventional dose of intrathecal hyperbaric bupivacaine in patient undergoing elective cesarean section. Methods: Seventy-four pregnant women aged 20-35 years old which underwent elective cesarean section at Chitwan Medical College were randomized into two groups. One group received spinal anesthesia with 8mg of0.5% hyperbaric bupivacaine and 25μg fentanyl and another group received 12mg 0.5% bupivacaine. Results: The mean age, baseline heart rate, systolic and diastolic blood pressure were comparable in both groups. Significant difference in hypotension (24.31% vs. 62.16%, p<0.05) and Nausea and vomiting (16.20% vs. 27%, p<0.05) were found in bupivacaine-fentanyl group versus a conventional dose of spinal bupivacaine group. Conclusions: Low dose of bupivacaine with Fentanyl provides good spinal anesthesia for cesarean section with less hypotension, nausea and vomiting in comparison to bupivacaine alone.